Catalyst for synthesizing multi-carbon product through electrocatalysis of CO2 and preparation method of catalyst

By modifying the anionic and cationic polymer coating on the surface of the Cu2O catalyst, the microenvironment of the catalyst is improved, which solves the problem of low selectivity of the Cu2O catalyst for the electroreduction of CO2 into multi-carbon products, and achieves efficient CO2RR and energy utilization efficiency.

CN119332297APending Publication Date: 2025-01-21ZHEJIANG WANLI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311162213.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing Cu2O catalysts have low selectivity for CO2 electroreduction into polycarbon products, and it is difficult to effectively inhibit the formation of C1 products and the degradation of water.

Method used

By modifying the anionic polymer coating (Speek coating) and the cationic polymer coating (Nafion coating) on ​​the surface of the Cu2O catalyst, the microenvironment of the catalyst is improved and the activity and selectivity of CO2RR are improved.

Benefits of technology

It significantly improves the Faradaic efficiency of C2+ products, enhances the energy efficiency of CO2 utilization, and effectively inhibits the formation of C1 products and the degradation of water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332297A_ABST
    Figure CN119332297A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for synthesizing a multi-carbon product by electrocatalysis of CO2, the catalyst is a Cu2O catalyst modified by an anionic polymer coating and a cationic polymer coating, the anionic polymer coating covers the surface of granular Cu2O, the particle size of the granular Cu2O is 3-7 [mu] m, the cationic polymer coating covers the surface of the anionic polymer coating, the particle size of the cationic polymer coating is 3-7 [mu] m, and the particle size of the cationic polymer coating is 3-7 [mu] m. The anionic polymer coating is a Speek coating, and the cationic polymer coating is a Nafion coating. The ionic polymer structure of the catalyst is elaborately designed in the preparation process, the Cu2O catalyst with a local high pH value, a high CO2 concentration and a hydrophobic microenvironment is obtained through elaborately designed steps and parameters, and when the Cu2O catalyst is applied to a carbon dioxide electrochemical reducing agent, the Cu2O catalyst has high electrocatalytic activity and selectivity on carbon dioxide reduction, and the Cu2O catalyst has a good application prospect. The Faraday efficiency of C2 + products can be remarkably improved, and the energy efficiency of CO2 utilization is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of CO2 electrochemical reduction, and specifically relates to a catalyst for electrocatalytic CO2 synthesis of multi-carbon products and a preparation method thereof. Background Art

[0002] Carbon dioxide is one of the major greenhouse gases and plays an important role in global climate change. Traditionally, carbon dioxide is regarded as a waste product and is emitted into the atmosphere. However, with the deepening of people's understanding of climate change, converting carbon dioxide into useful chemicals and fuels has become a viable approach. Electrocatalytic carbon dioxide reduction is a process that uses electrochemical methods to convert carbon dioxide into high-value-added carbon-based compounds. The most promising catalyst for CO2 reduction (CO2RR) is copper (Cu) because it can produce multi-carbon products (C 2+ Products) such as C2H4, C2H5OH, and C3H7OH, rather than those containing only one carbon atom (C1 products), such as HCOOH, CO, and CH4 or H2. Among these products, those containing two or more carbon atoms are the most desirable because they can be easily converted into value-added chemicals and liquid fuels through conventional thermal catalytic processes. 2+ products, it is necessary to reduce the formation of C1 products and minimize the conversion of the electrolyte solvent H2O to H2.

[0003] Recent studies have shown that the activity and selectivity of Cu2O for CO2RR can be further modified by introducing organic compounds on the Cu2O surface. These studies attributed the improved selectivity to the increased hydrophobicity and affinity for CO2 of the organic layer, which increases the CO2 / H2O ratio at the catalyst surface. Ion-conducting polymers (ionomers) can also modify the local concentrations of CO2, H2O, OH-, and H+, as their main chains containing -CH2- or -CF2- modulate the hydrophobicity and the charged moieties at the end of the side chains regulate ion transport. However, the effect of ionomers on CO2RR is still unclear.

[0004] Therefore, it is urgent to clarify the effect of ionomers on the local Cu2O catalyst microenvironment and promote the electrocatalytic synthesis of multi-carbon products from CO2. In view of this, the present invention provides a catalyst for electrocatalytic synthesis of multi-carbon products from CO2 and a preparation method thereof. Summary of the invention

[0005] In view of the technical problem that the existing Cu2O has low selectivity for CO2 electroreduction to multi-carbon products, the present invention provides a catalyst for electrocatalytic CO2 synthesis of multi-carbon products and a preparation method thereof. The catalyst uses an anionic and cationic polymer coating to improve the Cu2O microenvironment and has high electrocatalytic activity for CO2RR and high selectivity for C 2+The high selectivity of the products can promote the electrocatalytic synthesis of multi-carbon products from CO2, which can significantly increase the C 2+ The Faraday efficiency of the product improves the energy efficiency of CO2 utilization.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a catalyst for electrocatalytic CO2 synthesis of multi-carbon products, the catalyst is a Cu2O catalyst modified by an anionic polymer coating and a cationic polymer coating, the anionic polymer coating covers the surface of granular Cu2O, the particle size of the granular Cu2O is 3 to 7 μm, the cationic polymer coating covers the surface of the anionic polymer coating, the anionic polymer coating is a Speek coating, and the cationic polymer coating is a Nafion coating.

[0007] A method for preparing the above-mentioned catalyst for electrocatalytic CO2 synthesis of multi-carbon products. The catalyst is mainly synthesized by a two-step method, namely: first, a metal organic framework Mof-74 Cu is synthesized by a solvent thermal reaction, and then Cu2O powder is synthesized by a high-temperature pyrolysis method, and then a diluted Speek solution is dripped onto the surface of Cu2O by a drip coating method to form a Speek coating, and finally a diluted Nafion solution is dripped onto the surface of the Speek coating by a drip coating method to form a Nafion coating.

[0008] The preparation method of the catalyst for electrocatalytic CO2 synthesis of multi-carbon products specifically comprises the following steps:

[0009] (1) preparing a Mof-74 Cu precursor solution: dissolving a copper source and an organic ligand in a mixed solution of ethanol, N,N-dimethylformamide and deionized water to form a Mof-74 Cu precursor solution;

[0010] (2) Synthesis of the metal organic framework Mof-74 Cu: The Mof-74 Cu precursor solution is heated at 100-120°C for 18-24 hours to perform a solvothermal reaction; after the reaction is completed, the precipitate is collected by centrifugation, washed, and vacuum dried to obtain a powdered metal organic framework Mof-74 Cu;

[0011] (3) Synthesis of Cu2O powder: First, the powdered metal organic framework Mof-74 Cu and melamine are mixed, ground evenly, and then placed in a porcelain boat with a lid. The porcelain boat is then placed in a tube furnace and sintered at high temperature to obtain Cu2O powder.

[0012] (4) preparing a Cu2O catalyst precursor: first, mixing Cu2O powder with isopropanol, deionized water, and a 5% by mass Nafion solution to prepare a catalyst ink solution, then evenly drop-coating the catalyst ink solution on a carbon paper electrode substrate, and drying to obtain a Cu2O catalyst precursor for later use;

[0013] (5) Preparation of Cu2O catalyst: First, the Speek film is dissolved in N,N-dimethylacetamide to obtain a Speek diluent. After complete dissolution by ultrasonication, the Speek diluent is added dropwise to the Cu2O catalyst precursor. After drying, a Speek coating is formed on the surface of the Cu2O to obtain Cu2O / Speek. Subsequently, a Nafion solution with a mass fraction of 5% is added dropwise to the Cu2O / Speek. After drying, a Nafion coating is formed on the surface of the Speek coating to obtain a Cu2O / Speek / Nafion catalyst, i.e., a Cu2O catalyst.

[0014] Preferably, in step (1), the mass ratio of the copper source to the organic ligand is (0.1-2):2, and the volume ratio of N,N-dimethylformamide, ethanol and deionized water in the mixed solution is (10-15):1:1.

[0015] Furthermore, in step (1), the mass ratio of the copper source to the organic ligand is 1:2.

[0016] Preferably, in step (1), the copper source is one of CuCl2·2H2O, Cu(NO3)3·3H2O, and CuSO4·5H2O, and the organic ligand is 2,5-dihydroxyterephthalic acid.

[0017] Preferably, in step (2), the centrifugal speed of the centrifugal separation is 7000-9000 rpm, the washing is performed by washing with acetone and deionized water three times respectively, and the vacuum drying time is 24-36 hours.

[0018] Preferably, in step (3), the mass ratio of the powdered metal organic framework Mof-74 Cu to melamine is (3-4):(6-8), and the high temperature sintering process is: heating to 900-1000°C at a rate of 3-5°C / min, maintaining at 900-1000°C for 2-3h, and naturally cooling to obtain Cu2O powder.

[0019] Preferably, in step (4), the mass of Cu2O powder is 0.01-0.02 g, the volume of Nafion solution is 0.05-0.1 mL, the volume of isopropanol is 0.3-0.4 mL, and the volume of deionized water is 0.6-0.7 mL.

[0020] Furthermore, in step (5), 30 to 50 μL of Speek dilution solution is dripped onto the Cu2O catalyst precursor, and after drying, Cu2O / Speek is obtained, and then 30 to 50 μL of Nafion solution is dripped onto the Cu2O / Speek.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The catalyst of the present invention is a Cu2O catalyst modified by an anionic polymer coating (Speek coating) and a cationic polymer coating (Nafion coating). During the CO2RR application process, the inner Speek coating can effectively activate CO2 molecules and act as a buffer layer for OH-, avoiding the enrichment of carbonates that hinder the active sites of the catalyst; the outer Nafion coating also has hydrophobicity induced by the -CF2- main chain, which can create a hydrophobic environment on the catalyst surface, thereby increasing the CO2 concentration on the catalyst surface. And due to the cationic permselectivity of the Nafion coating, the OH- generated in situ by CO2RR is limited, thereby creating a local high pH environment for the catalyst. In summary, the Speek coating and the Nafion coating create a microenvironment with a local high pH value and a high CO2 concentration. Due to the local high pH value, high CO2 concentration and hydrophobic microenvironment, the Cu2O catalyst is conducive to promoting subsequent CC bond coupling, thereby highly selectively catalyzing the reduction of CO2 to synthesize C 2+ products and inhibit the hydrogen evolution reaction.

[0023] 2. The present invention carefully designs the ion polymer structure of the catalyst during the preparation process. Through carefully designed steps and parameters, a Cu2O catalyst with a local high pH value, high CO2 concentration and a hydrophobic microenvironment is obtained. When used as a carbon dioxide electrochemical reductant, it has high electrocatalytic activity and selectivity for carbon dioxide reduction, which can significantly improve C 2+ The Faraday efficiency of the product improves the energy efficiency of CO2 utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Surface analysis and depth profiling of the copper element in the Cu2O catalyst precursor and the Cu2O / Speek / Nafion catalyst prepared in step (4) of Example 1 of the present invention by secondary ion mass spectrometry (SIMS);

[0025] Figure 2 Surface analysis and depth profiling of the Cu2O catalyst precursor and the Cu2O / Speek / Nafion catalyst potassium in the Cu2O / Speek / Nafion catalyst prepared in step (4) of Example 1 of the present invention by secondary ion mass spectrometry (SIMS);

[0026] Figure 3Surface analysis and depth profiling of the sulfur element in the Cu2O catalyst precursor and the Cu2O / Speek / Nafion catalyst prepared in step (4) of Example 1 of the present invention by secondary ion mass spectrometry (SIMS);

[0027] Figure 4 The catalytic performance (voltage-Faraday efficiency diagram) of the Cu2O catalyst precursor performance test diagram prepared in step (4) of Example 1 of the present invention;

[0028] Figure 5 This is the catalytic performance (voltage-Faraday efficiency diagram) of the Cu2O / Speek / Nafion catalyst performance test diagram prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the accompanying drawings.

[0030] The method for preparing a catalyst for electrocatalytic CO2 synthesis of multi-carbon products of Example 1 comprises the following steps:

[0031] (1) Preparation of Mof-74 Cu precursor solution: 0.08 g of Cu(NO3)3·3H2O and 0.04 g of N,N-dimethylformamide were ultrasonically dissolved in a mixed solution containing 15 mL of N,N-dimethylformamide, 1 mL of ethanol and 1 mL of deionized water. The green solution formed was the Mof-74 Cu precursor solution.

[0032] (2) Synthesis of metal organic framework Mof-74 Cu: The Mof-74 Cu precursor solution obtained in step (1) was heated at 120° C. for 24 h to perform a solvothermal reaction; after the reaction, the brown product was separated by centrifugation, washed three times with acetone and deionized water respectively, and then dried in a vacuum oven at 60° C. for 24 h to obtain a powdered metal organic framework Mof-74 Cu;

[0033] (3) Synthesis of Cu2O powder: First, 290 mg of the powdered metal organic framework Mof-74Cu obtained in step (2) was mixed with 660 mg of melamine, and after being ground evenly, the mixture was placed in a porcelain boat with a lid, and then the porcelain boat was placed in a tube furnace, and the temperature was raised to 1000°C at a rate of 5°C / min in a N2 atmosphere, maintained at 1000°C for 2 h, and cooled naturally to obtain Cu2O powder;

[0034] (4) Preparation of Cu2O catalyst precursor: First, 0.01 g of the Cu2O powder obtained in step (3) was mixed in a mixed solution containing 0.7 mL of isopropanol, 0.3 mL of deionized water, and 0.08 mL of a 5% Nafion solution, and ultrasonicated for 15 min to prepare a catalyst ink solution. Then, 0.1 mL of the catalyst ink solution was evenly dropped on a carbon paper electrode substrate, and dried in a vacuum drying oven overnight to obtain a Cu2O catalyst precursor for later use; wherein the carbon paper electrode area is approximately 1*1 cm 2 , the Cu2O loading on the carbon paper electrode is about 1 mg;

[0035] (5) Preparation of Cu2O catalyst: First, 0.1 g of Speek film was dissolved in 5 mL of N,N-dimethylacetamide to obtain Speek diluent. After complete dissolution by ultrasonication, 30 μL of Speek diluent was added dropwise to the Cu2O catalyst precursor. After drying, a Speek coating was formed on the surface of Cu2O to obtain Cu2O / Speek. Subsequently, 30 μL of a Nafion solution with a mass fraction of 5% was added dropwise to the Cu2O / Speek. After drying, a Nafion coating was formed on the surface of the Speek coating to obtain a Cu2O / Speek / Nafion catalyst, i.e., a Cu2O catalyst.

[0036] Figure 1 Surface analysis and depth profiling of the copper element in the Cu2O catalyst precursor and the Cu2O / Speek / Nafion catalyst prepared in step (4) of Example 1 of the present invention by secondary ion mass spectrometry (SIMS). The etching depth with an etching time of 100 s is recorded as h1, and the etching depth with an etching time of 400 s is recorded as h2.

[0037] pass Figure 1 The depth analysis of copper element by secondary ion mass spectrometry (SIMS) showed that the copper content in the Cu2O / Speek / Nafion catalyst gradually increased when the etching time was 0-400s; after the etching time was 400s, the copper element in the Cu2O / Speek / Nafion catalyst remained basically unchanged. However, for the Cu2O catalyst precursor, the copper element has stabilized when the etching time is 100s, which proves that the Cu2O layer (Cu2O particles) of the Cu2O / Speek / Nafion catalyst is located at a distance of h2 or deeper from the catalyst surface.

[0038] Figure 2 Surface analysis and depth profiling of the Cu2O catalyst precursor and the Cu2O / Speek / Nafion catalyst prepared in step (4) of Example 1 of the present invention using secondary ion mass spectrometry (SIMS).

[0039] pass Figure 2 The depth analysis of the secondary ion mass spectrometry (SIMS) of potassium element showed that the potassium content in the Cu2O / Speek / Nafion catalyst reached a peak before the etching time was 400s, but the Cu2O catalyst precursor did not have potassium element. This is because only the Speek coating has potassium element. Therefore, this proves that the Speek coating of the Cu2O / Speek / Nafion catalyst is located at a distance of h1 to h2 from the catalyst surface.

[0040] Figure 3 Surface analysis and depth profiling of the sulfur element in the Cu2O catalyst precursor and the Cu2O / Speek / Nafion catalyst prepared in step (4) of Example 1 of the present invention by secondary ion mass spectrometry (SIMS).

[0041] like Figure 3 As shown, the sulfur element in the Cu2O / Speek / Nafion catalyst reaches peak values ​​at etching times of 100s and 400s, respectively. Since the S content of the Speek coating is higher than that of the Nafion coating, this proves that the Nafion coating of the Cu2O / Speek / Nafion catalyst is located from the catalyst surface to a distance h1 from the catalyst surface, and the Speek coating is located from a distance h1 to a distance h2 from the catalyst surface.

[0042] comprehensive Figure 1 to Figure 3 From the conclusion, it can be known that the Cu2O / Speek / Nafion catalyst is a layered catalyst, and its Cu2O layer, Speek coating and Nafion coating are distributed from the inside to the outside.

[0043] Figure 4 The catalytic performance (voltage-Faraday efficiency diagram) of the Cu2O catalyst precursor performance test diagram prepared in step (4) of Example 1 of the present invention.

[0044] like Figure 4 As shown in the figure, within the applied voltage range, the selectivity of the Cu2O catalyst precursor to multi-carbon products (FE C2H4 ) reached 58% at a potential of -1.13 V vs. RHE, accompanied by the generation of methane, carbon monoxide and hydrogen, and the selectivity of multi-carbon products of the Cu2O catalyst precursor was not high.

[0045] Figure 5 This is the catalytic performance (voltage-Faraday efficiency diagram) of the Cu2O / Speek / Nafion catalyst performance test diagram prepared in Example 1 of the present invention.

[0046] like Figure 5As shown in Figure 2, the selectivity of Cu2O / Speek / Nafion catalyst for multi-carbon products (FE C2H4 ) is as high as 85%, accompanied by the generation of a small amount of methane, carbon monoxide and hydrogen. Compared with the Cu2O catalyst precursor, the selectivity of multi-carbon products of Cu2O / Speek / Nafion catalyst is greatly improved.

Claims

1. A catalyst for electrocatalytic synthesis of multi-carbon products from CO2, characterized in that: The catalyst is a Cu2O catalyst modified by an anionic polymer coating and a cationic polymer coating. The anionic polymer coating covers the surface of the granular Cu2O, the particle size of the granular Cu2O is 3-7 μm, the cationic polymer coating covers the surface of the anionic polymer coating, the anionic polymer coating is a Speek coating, and the cationic polymer coating is a Nafion coating.

2. A method for preparing a catalyst for electrocatalytic CO2 synthesis of multi-carbon products according to claim 1, characterized in that: The catalyst is mainly synthesized by a two-step method, namely: first, a metal organic framework Mof-74 Cu is synthesized by a solvent thermal reaction, then Cu2O powder is synthesized by a high-temperature pyrolysis method, and then a diluted Speek solution is dripped onto the surface of Cu2O by a drop coating method to form a Speek coating, and finally a diluted Nafion solution is dripped onto the surface of the Speek coating by a drop coating method to form a Nafion coating.

3. The preparation method according to claim 2, characterized in that: The specific steps include: (1) preparing a Mof-74 Cu precursor solution: dissolving a copper source and an organic ligand in a mixed solution of ethanol, N,N-dimethylformamide and deionized water to form a Mof-74 Cu precursor solution; (2) Synthesis of the metal organic framework Mof-74 Cu: The Mof-74 Cu precursor solution is heated at 100-120°C for 18-24 hours to perform a solvothermal reaction; after the reaction is completed, the precipitate is collected by centrifugation, washed, and vacuum dried to obtain a powdered metal organic framework Mof-74 Cu; (3) Synthesis of Cu2O powder: First, the powdered metal organic framework Mof-74 Cu and melamine are mixed, ground evenly, and then placed in a porcelain boat with a lid. The porcelain boat is then placed in a tube furnace and sintered at high temperature to obtain Cu2O powder. (4) preparing a Cu2O catalyst precursor: first, mixing Cu2O powder with isopropanol, deionized water, and a 5% by mass Nafion solution to prepare a catalyst ink solution, then evenly drop-coating the catalyst ink solution on a carbon paper electrode substrate, and drying to obtain a Cu2O catalyst precursor for later use; (5) Preparation of Cu2O catalyst: First, the Speek film is dissolved in N,N-dimethylacetamide to obtain a Speek diluent. After complete dissolution by ultrasonication, the Speek diluent is added dropwise to the Cu2O catalyst precursor. After drying, a Speek coating is formed on the surface of the Cu2O to obtain Cu2O / Speek. Subsequently, a Nafion solution with a mass fraction of 5% is added dropwise to the Cu2O / Speek. After drying, a Nafion coating is formed on the surface of the Speek coating to obtain a Cu2O / Speek / Nafion catalyst, i.e., a Cu2O catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the copper source to the organic ligand is (0.1-2):2, and the volume ratio of N,N-dimethylformamide, ethanol and deionized water in the mixed solution is (10-15):1:

1.

5. The preparation method according to claim 4, characterized in that: In step (1), the mass ratio of the copper source to the organic ligand is 1:

2.

6. The preparation method according to any one of claims 3 to 5, characterized in that: In step (1), the copper source is one of CuCl2·2H2O, Cu(NO3)3·3H2O, and CuSO4·5H2O, and the organic ligand is 2,5-dihydroxyterephthalic acid.

7. The preparation method according to claim 3, characterized in that: In step (2), the centrifugal speed of the centrifugal separation is 7000-9000 rpm, the washing is performed by washing with acetone and deionized water three times respectively, and the vacuum drying time is 24-36 hours.

8. The preparation method according to claim 3, characterized in that: In step (3), the mass ratio of the powdered metal organic framework Mof-74 Cu to melamine is (3-4):(6-8), and the high temperature sintering process is: heating to 900-1000°C at a rate of 3-5°C / min, maintaining at 900-1000°C for 2-3h, and naturally cooling to obtain Cu2O powder.

9. The preparation method according to claim 3, characterized in that: In step (4), the mass of Cu2O powder is 0.01-0.02 g, the volume of Nafion solution is 0.05-0.1 mL, the volume of isopropanol is 0.3-0.4 mL, and the volume of deionized water is 0.6-0.7 mL.

10. The preparation method according to claim 9, characterized in that: In step (5), 30 to 50 μL of Speek dilution solution is added dropwise onto the Cu2O catalyst precursor, and after drying, Cu2O / Speek is obtained, and then 30 to 50 μL of Nafion solution is added dropwise onto the Cu2O / Speek.

Citation Information

Cited By

  • Preparation method and application of mixed ionomer modified cuprous oxide catalyst

    CN120519913A